The Secrets to MIMIKATZ - The Credential Dumper: Shairoze Malik, Erej Azeem - Shairoze Malik,; Erej Azeem, (International Journal for Electronic Crime Investigation, 2021)
With the emergence of many credential dumping tools, Mimikatz has become an exceedingly dramatic tool against Windows users that allows intruders to fetch plain text passwords. Moreover they also target memory to dump password hashes. Mimikatz capacity and potential will be briefly discussed throughout the paper. Several modules of Mimikatz to dump credentials will follow, and the paper will conclude with procedures and techniques that may be used as prevention against Mimikatz attacks that are performed.